The Characteristics of Smart Society in the Context of Public Governance Modernization - Sveklaitė, Lina; Stasiukynas, Andrius (Jaunųjų mokslininkų darbai, 2015)
Changing social conditions and technology advancement call for public governance modernization with focus on public involvement, citizen participation and collaborative policy-making. Citizen engagement and empowerment facilitate the new public governance. Nowadays much attention is paid to building a knowledge society, new knowledge creation, its use and dissemination. Seeking to implement the ideas of the new public governance it is necessary to clarify and analyze the characteristics of the smart society and the principles of public governance in a wider context. The aim of the research is to identify the characteristics of the smart society in the context of public governance modernization. Research tasks: 1) to define the evolution of the new public governance; 2) to clarify the characteristics of society in the context of the new public governance; 3) to define the role of social networks while building the smart society. Research methods: comparative analysis of scientific literature, data systematization. The interaction between the new public governance and the smart society through social networks was analysed in the paper. It was found that the following should be implemented so as to build the smart society: lifelong learning, collaboration, partnership, common goals, access to information, participation, citizenship, high technology.